Specific Profiles and Amplification of Resistance to Anti-tuberculosis Drugs in Tuberculosis Patients in the Republic of Karelia - Yu. M. Markelov; E. N. Belyaeva; T. V. Sunchalina (Туберкулез и болезни лёгких)
The objective: to determine the frequency of resistance of Mycobacterium tuberculosis (MTB) to the most effective anti-tuberculosis drugs in tuberculosis patients in the Republic of Karelia, to characterize cases of amplification of MTB drug resistance during chemotherapy (CT).Subjects and Methods. MTB cultures of 1,137 tuberculosis patients were studied, the patients received chemotherapy from 2016 to 2021, among them 634 (55.8%) had multiple drug resistance (MDR). Among MBT cultures with MDR, there was a high frequency of MTB with extensive drug resistance (XDR) – 42.3% (268/634) including new cases. It provided a negative impact on the chemotherapy efficacy. Most often, amplification of MTB drug resistance was observed in patients treated as per regimen IV – 37/49 (75.5%) cases. MTB drug resistance amplified more often in the cases who were already resistant to 3 and more anti-tuberculosis drugs, 31/49 (63.3%). Most often, amplification was noted in aminoglycosides (Km, Am) and glycopeptide (Cm), (71.6% of cases). The high frequency of MTB drug resistance amplification from MDR up to XDR was due to the lack of rapid molecular genetic methods to test drug susceptibility to fluoroquinolones and aminoglycosides.